Effect of Fatty Acyl Group and Sterol Composition on Sensitivity of Lecithin Liposomes to Imidazole Antimycotics - Yamaguchi, Hideyo (1979)
The specific affinity for membrane lipids and the membrane selectivity of three imidazole derivatives, clotrimazole, miconazole, and econazole, were studied using various types of liposomes with respect to the lecithin fatty acyl group composition and the liposome content and composition of sterol as membrane models. The sensitivity of liposomes to these drugs was primarily dependent upon the lecithin fatty acyl group composition. With sterol-free liposome systems, each imidazole induced maximum release of trapped glucose as a marker from the unsaturated dioleoyl lecithin liposomes, minimum release from the saturated dipalmitoyl lecithin liposomes, and intermediate release from egg lecithin liposomes. The sensitivity of the dipalmitoyl lecithin liposomes to any imidazole drug was not influenced by the incorporation of cholesterol or ergosterol. On the other hand, clotrimazole-induced permeability changes of liposomes prepared from unsaturated dioleoyl lecithin or egg lecithin were greatly enhanced by the incorporation of ergosterol, whereas they were suppressed by cholesterol incorporation. The sensitivity of liposomes prepared from these unsaturated lecithins to miconazole and econazole was also augmented by ergosterol incorporation, although it was scarcely altered by cholesterol incorporation. Negatively charged liposomes were more sensitive to the three imidazole drugs than positively charged liposomes.